Social Interactions between Teachers and Students: A Study Addressing Associations and Predictions - Mariano, Marília; Bolsoni-silva, Alessandra Turini (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, 2018)
Abstract Interactions between teachers and students impact children’s academic and social learning. This study’s objective was to identify associations and predictions between variables concerning social educational skills, negative educational practices, behavior problems and the social skills of students differentiated by schooling, clinical indicators of behavior problems, and gender. A total of 283 children and their teachers from the public schools participated in the study, who answered questionnaires and participated in a semi-structured interview. Correlation and regression statistical analysis were performed. All the groups presented positive correlations between social educational skills, children’s social skills, negative educational practices, and behavior problems. Behavior problems and social skills presented predictive values among preschoolers. The aforementioned variables, together with positive and negative educational practices, presented predictive values among school children. The conclusion is that teachers can be a protective factor for children’s development, but this requires planning.

Resumen Interacciones entre profesores y alumnos producen impactos en los aprendizajes académicos y sociales de los niños. El objetivo de este estudio fue identificar asociaciones y predicciones entre variables de habilidades sociales educativas, prácticas educativas negativas, problemas conductuales y habilidades sociales infantiles, de alumnos diferenciados por la escolaridad, indicadores clínicos de problemas conductuales y sexo. Participaron del estudio 283 niños y sus profesores, de la red pública de enseñanza, que contestaron cuestionarios y participaron de entrevista semiestructurada. Se llevaron a cabo análisis estadísticos de correlación y regresión. En todos los grupos, fueron encontradas correlaciones positivas entre habilidades sociales educativas y infantiles y prácticas educativas negativas y problemas conductuales. Para preescolares, las quejas de problemas y las habilidades sociales presentaron valores predictivos. Para escolares, estas variables, sumadas a las prácticas educativas positivas y negativas, indicaron valores predictivos. Se concluye que profesores pueden actuar como factor protector al desarrollo, lo que demanda planeamiento.

Resumo Interações entre professores e alunos produzem impactos nas aprendizagens acadêmica e social das crianças. Este estudo objetivou identificar associações e predições entre variáveis de habilidades sociais educativas, práticas educativas negativas, problemas de comportamentos e habilidades sociais infantis de alunos diferenciados pela escolaridade, indicadores clínicos de problemas de comportamento e sexo. Participaram do estudo 283 crianças da rede pública de ensino e seus professores que responderam a questionários e participaram de entrevista semiestruturada. Conduziram-se análises estatísticas de correlação e regressão. Em todos os grupos houve correlações positivas entre habilidades sociais educativas e infantis e práticas educativas negativas e problemas de comportamento. Para pré-escolares, as queixas de problemas e as habilidades sociais apresentaram valores preditivos. Para escolares, as variáveis supracitadas, somadas às práticas educativas positivas e negativas, indicaram valores preditivos. Conclui-se que professores podem atuar como fator protetivo ao desenvolvimento infantil, o que requer planejamento.
Interacciones Sociales entre Profesores y Alumnos: Un Estudio de Asociaciones y Predicciones
Interações Sociais entre Professores e Alunos: Um Estudo de Associações e Predições
Keywords: behavioral disorders; social skills; teacher attitudes; distúrbios do comportamento; habilidades sociais; atitudes do professor